Evolution of concepts of personnel competence development - Чорний, А. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
This study was conducted through the importance of linking the concepts of corporate learning organization among themselves and a small number of published research on this issue. The answer to this question will allow the heads of the corporate learning departments to better assess their own units, select the necessary forms of development, and effectively associate them with the corporate LMS (learning management system), as well as formulate a strategy for developing training tools with a focus on more recent ones.In order to realize the corresponding task - methods of analysis and synthesis were used, a review of existing formats and forms of development of professional competencies was conducted, a survey of specialists and managers of IT companies in Kyiv was conducted and the obtained results were analyzed.The paper examines the evolution of modern concepts of staff competence development and highlights the main stages: e-learning, mixed learning, lifelong learning, digital learning. The main formats are considered, in which the tools of competence development of the personnel are used: traditional formats, corporate university, corporate e-university, experimental training, macro education, micro curriculum. The definition of such formats as macro education and experimental learning is proposed.The description of tools for development of professional competencies is presented: MBA, conferences, articles, certifications, books; trainings, cinema clubs, quests; coaching, mentoring, rotation, coaching, buddying, shadowing, statement; MOOC; video channels, mutual learning, chats in soc. networks, SMS-training.The role of the learning management system (LMS) in each of the described concepts has been investigated, and the conformity of traditional forms of learning with their analogues with the use of information technologies is indicated.The main result of the study is the developed model of the evolution of the concepts of competence development within corporate learning.